Microsoft 70-410 : installing and configuring Windows Server 2012 R2 - Sutton, Darin; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"This course is designed for Information Technology (IT) professionals, who have Windows Server 2012 operating system knowledge and experience and want to validate the skills and knowledge necessary to implement the Windows Server 2012 core infrastructure services. This course is part one of a series of courses which validate the skills and knowledge necessary to implement a core Windows Server 2012 Infrastructure into an existing enterprise environment. This initial course will validate the initial implementation and configuration of the Windows Server 2012 core services, such as Active Directory and the networking services."--Resource description page.
Presenter, Darin Sutton.
Title and publication information from resource description page (Safari, viewed April 6, 2017).
Presenter's name from title screen.
Keywords: Microsoft Windows server -- Certification -- Study guides; Client/server computing -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books